2010
DOI: 10.1016/j.watres.2010.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community dynamics in horizontal flow constructed wetlands with different plants for high salinity industrial wastewater polishing

Abstract: This study is focused on the diversity of bacterial communities from two series of horizontal subsurface flow constructed wetlands (CW) polishing high salinity tannery wastewater. Each series was planted with Arundo donax or Sarcocornia sp. in a substrate composed by expanded clay and sand. Chemical and biochemical oxygen demand removal efficiencies were similar in each series, varying between 58 and 67% (inlet COD 218 ± 28 mg L(-1)) and 60 and 77% (inlet BOD(5) 37 ± 6 mg L(-1)), respectively. High numbers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 18 publications
2
31
0
3
Order By: Relevance
“…Initially, the water in each microcosm was completely drained through the bottom valve. Sand from a depth of 5 to 10 cm was collected at five different locations (four corners and the center of the microcosms) (Calheiros et al 2010;Wu et al 2013) in each parallel and then mixed into a composite sample. The sand samples from the three parallel microcosms were subsequently combined into a composite sample before DNA extraction.…”
Section: Microbial Samplingmentioning
confidence: 99%
“…Initially, the water in each microcosm was completely drained through the bottom valve. Sand from a depth of 5 to 10 cm was collected at five different locations (four corners and the center of the microcosms) (Calheiros et al 2010;Wu et al 2013) in each parallel and then mixed into a composite sample. The sand samples from the three parallel microcosms were subsequently combined into a composite sample before DNA extraction.…”
Section: Microbial Samplingmentioning
confidence: 99%
“…First, each microcosm was completely drained. Sand samples were then collected from the top layer 5-10 cm deep at five different plots (Calheiros et al, 2010) in each parallel and then mixed into a composite sample. The sand samples were stored in 5 mL aseptic Eppendorf tubes, immediately placed on ice and stored at À80 C before microbial analysis.…”
Section: Samplingmentioning
confidence: 99%
“…Most of these studies reported that plants had little or no effect on the community structure or abundance of the overall bacteria (Ahn et al, 2007;Baptista et al, 2008) or particular functional groups, such as the ammonia oxidizing bacteria (Gorra et al, 2007), sulfate reducing bacteria (Baptista et al, 2008), and methane oxidizing communities (DeJournett et al, 2007). However, several studies revealed that the presence of plants had a significant effect on the species richness and the structure of bacterial communities in CWs (Calheiros et al, 2009(Calheiros et al, , 2010. To date, studies conducted to assess how plants affect the microbial community structure in CWs have used conventional molecular biology methods (e.g., PCR-DGGE and FISH).…”
Section: Introductionmentioning
confidence: 99%